2007
DOI: 10.1521/aeap.2007.19.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of New Sexual Partners Among Women With HIV Infection: Patterns of Disclosure and Sexual Behavior within New Partnerships

Abstract: These findings highlight the importance of ongoing support for sexual risk reduction among women with HIV-infection and for strategies that reduce the strength of relationships between ART beliefs and sexual risk behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Such an approach would (1) step-up efforts to educate all MSM about the seriousness of HIV infection and the need to continue to practice safer sex whenever possible. Older MSM no longer have the constant reminder of seeing their friends and associates dying of AIDS, whereas many younger MSM did not experience this at all; (2) continue to stress the importance of HIV antibody testing, contact referral or tracking and seeking treatment as early as possible in order to reduce both the sequelae of HIV infection and the possibility of newly infected men transmitting HIV to their sexual partners before they know that they have been infected; and (3) at the same time, mount energetic campaigns to counter the increasingly prevalent attitudes of reduced HIV concern and safer sex fatigue seen among homosexually active men, women (Wilson et al, 2007) and IDUs (Tun et al, 2003).…”
Section: Hiv-seropositivementioning
confidence: 99%
“…Such an approach would (1) step-up efforts to educate all MSM about the seriousness of HIV infection and the need to continue to practice safer sex whenever possible. Older MSM no longer have the constant reminder of seeing their friends and associates dying of AIDS, whereas many younger MSM did not experience this at all; (2) continue to stress the importance of HIV antibody testing, contact referral or tracking and seeking treatment as early as possible in order to reduce both the sequelae of HIV infection and the possibility of newly infected men transmitting HIV to their sexual partners before they know that they have been infected; and (3) at the same time, mount energetic campaigns to counter the increasingly prevalent attitudes of reduced HIV concern and safer sex fatigue seen among homosexually active men, women (Wilson et al, 2007) and IDUs (Tun et al, 2003).…”
Section: Hiv-seropositivementioning
confidence: 99%
“…An ongoing challenge to secondary prevention of HIV is understanding and intervening with factors influencing continued engagement in unprotected sex with new and existing partners. [1][2][3] HIV-positive women with childhood abuse histories, including both physical and sexual abuse in childhood, have been identified as a particularly vulnerable population, with higher rates of unprotected sex, greater numbers of partners, and additional health risk behaviors, such as substance use, and poorer adherence than their counterparts without abuse histories. [4][5][6][7][8][9] One potentially relevant mechanism linking abuse and engagement in unprotected sex is disclosure of HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study published in 2007, 25.7% of women interviewed (n 5 74) chose to become pregnant after diagnosis with HIV (Craft, Delaney, Bautista, & Serovich, 2007). Other studies have reported that women with HIV are comparable to women without HIV in relation to conceiving and/or terminating a pregnancy (Ahluwalia, DeVellis, & Thomas, 1998;Wilson et al 2007). Richter, Sowell, and Pluto (2002) reported that women living with HIV desired pregnancy and were committed to becoming mothers.…”
mentioning
confidence: 99%